2009
DOI: 10.1039/b910015f
|View full text |Cite
|
Sign up to set email alerts
|

Homophymines B–E and A1–E1, a family of bioactive cyclodepsipeptides from the sponge Homophymia sp.

Abstract: Nine new cyclodepsipeptides, homophymines B-E (2-5) and A1-E1 (1a-5a), were isolated from the polar extracts of the sponge Homophymia sp. The new structures, featuring new polyketide-derived end groups, were determined by interpretation of NMR and MS data. The configurations of the new end groups was secured by the application of J-based configurational analysis. Homophymines displayed very potent antiproliferative activity (IC(50) in the nM range) against a panel of human cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…This b-branched framework, which characterizes all the members of this new class of non-ribosomal cyclodepsipeptides 5 , comprises the following: a 22-or a 25-membered macrolactone; the presence of complex and rare amino acids; a branching position occupied by a D-allo-b-hydroxy-a-amino acid acylated by the unique (2S,3S,4R)-3,4-dimethylglutamine (diMeGln) residue; and an N-terminus coupled to a saturated or unsaturated b-hydroxy acid. Examples of members of this family include callipeltin A 6 , papuamides 7,8 , neamphamides [9][10][11] , theopapuamides 12,13 , mirabamides 14,15 and homophymines 16,17 . Of note, all of them show relevant therapeutic profiles, mostly including potent cytotoxic and anti-HIV activities.…”
mentioning
confidence: 99%
“…This b-branched framework, which characterizes all the members of this new class of non-ribosomal cyclodepsipeptides 5 , comprises the following: a 22-or a 25-membered macrolactone; the presence of complex and rare amino acids; a branching position occupied by a D-allo-b-hydroxy-a-amino acid acylated by the unique (2S,3S,4R)-3,4-dimethylglutamine (diMeGln) residue; and an N-terminus coupled to a saturated or unsaturated b-hydroxy acid. Examples of members of this family include callipeltin A 6 , papuamides 7,8 , neamphamides [9][10][11] , theopapuamides 12,13 , mirabamides 14,15 and homophymines 16,17 . Of note, all of them show relevant therapeutic profiles, mostly including potent cytotoxic and anti-HIV activities.…”
mentioning
confidence: 99%
“…Two new saponins from Parthenium hysterophorus were found to be potent TNF-inhibitors (Shah et al, 2009). The successful isolation and structure determination of new cyclodepsipeptides has been reported (Zampella et al, 2009). These compounds, named homophymine B-E and A1-E1, were shown to exhibit potent anti-proliferative effects against several human cancer cell lines.…”
Section: Natural Products -Isolation Synthesis and Biosynthesismentioning
confidence: 99%
“…Chart 4. Synthesis of (2R,3R,4R)-2-Amino-3-hydroxy-4,5-dimethylhexanoic Acid (2) prepared from [RuCl 2 (C 6 H 6 )] 2 (48 mg, 0.096 mmol) and (R)-BINAP (121 mg, 0.195 mmol) according to the literature procedure.…”
Section: (R)-45-dimethyl-3-oxo-hexanoic Acid Methyl Ester (9)mentioning
confidence: 99%
“…Homophymine A (1) is known to exhibit cytoprotective activity against human immunodeficiency virus-1 (HIV-1) infection and moderate cytotoxicity. As part of the study on synthesizing bioactive cyclodepsipeptides of marine origin, [4][5][6][7][8] we focused on homophymine A, which contains (2R,3R,4R,6R)-3-hydroxy-2,4,6-trimethyloctanoic acid 9) and novel amino acid residues: (2S,3S,4R)-3,4-dimethylglutamine, 10,11) (2R,3R,4S)-4-amino-2,3-dihydroxy-1,7-heptandioic acid, and (2R,3R,4R)-2-amino-3-hydroxy-4,5-dimethylhexanoic acid (2). In earlier studies, we demonstrated that the asymmetric hydrogenation of α-amino-β-keto esters using chiral catalysts anti-selectively proceeds to afford anti β-hydroxy-α-amino acids in a high diastereo-and enantioselective manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation